2017
DOI: 10.1111/joa.12597
|View full text |Cite
|
Sign up to set email alerts
|

Histology and ultrastructure of the thymus during development in tilapia, Oreochromis niloticus

Abstract: The thymus in teleost fishes plays an important role in producing functionally competent T-lymphocytes. However, the thymus in tilapia is not well known, which greatly hampers investigations into the immune responses of tilapia infected by aquatic pathogens. The histological structure and ultrastructure of the thymus in Oreochromis niloticus, including embryos and larvae at different developmental stages, juveniles, and adult fish, were systematically investigated using whole mount in situ hybridization (WISH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 58 publications
6
14
0
Order By: Relevance
“…The epithelial capsule lining the apical surface facing the gill chamber contained mucous cells, in which the secretory material was stained positively with PAS and AB. Similar to the observations made herein, the thymic epithelium was also observed to comprise a large number of mucous cells in clingfish ( Sicyases sanguineus ) (Gorgollon, 1983), rainbow trout (Chilmonczyk, 1992), mandarin fish ( Siniperca chuatsi ) (Xie et al, 2006) and tilapia ( Oreochromis niloticus ) (Cao et al., 2017). The abundant mucous cells in the surface epithelium of thymus could constitute an immune barrier and protect the organ against microbial attacks and infections sourced from aquatic environments (Lazado & Caipang, 2014).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The epithelial capsule lining the apical surface facing the gill chamber contained mucous cells, in which the secretory material was stained positively with PAS and AB. Similar to the observations made herein, the thymic epithelium was also observed to comprise a large number of mucous cells in clingfish ( Sicyases sanguineus ) (Gorgollon, 1983), rainbow trout (Chilmonczyk, 1992), mandarin fish ( Siniperca chuatsi ) (Xie et al, 2006) and tilapia ( Oreochromis niloticus ) (Cao et al., 2017). The abundant mucous cells in the surface epithelium of thymus could constitute an immune barrier and protect the organ against microbial attacks and infections sourced from aquatic environments (Lazado & Caipang, 2014).…”
Section: Discussionsupporting
confidence: 77%
“…It was proposed that those supporting cells synthesise factors that provide thymocyte maturation and the acquisition of thymocyte immune characteristics (Chilmonczyk, 1992). As determined in this study, myoid cells have been reported in some fish, including Rutilus rutilus (Zapata, 1981a), rainbow trout (Chilmonczyk, 1983), seabream ( Diplodus puntazzo ) (Romano et al., 1999), juvenile Australian lungfish ( Neoceratodus forsteri ) (Mohammad et al., 2007), tilapia ( Oreochromis niloticus ) (Attia et al., 2010; Cao et al., 2017) and flounder ( Paralichthys olivaceus ) (Liu et al., 2004). Rimmer (1980) discussed the role that myoid cells might play as a local source of antigenic for self‐recognition, which increased the number of those cells and was related to the autoimmune disease myasthenia gravis.…”
Section: Discussionsupporting
confidence: 56%
“…In addition to the conventional mTECs described above, the thymic medulla contains unique structures called Hassall’s corpuscles (HCs). These structures, firstly characterized in 1846 by Arthur Hill Hassall ( 38 ) in human thymi have, after their initial description, been found in several other mammals ( 39 ) but as well as in bird and fish species ( 40 , 41 ). In humans, the HCs appear as a concentric merged cluster of unnucleated cells with a typical diameter of 20-100 μm and are present in large quantities already by the 28 th week of prenatal development ( 42 ).…”
Section: The Aire+ Mtecs Post-aire Mtecs and Hassall’s Corpusclesmentioning
confidence: 95%
“…RAG1 is the first immune gene expressed at the levels of embryo and larvae in vertebrate animals and expressed by the thymus organ when B cells and T cells were immature (Corripio-Miyar, Bird, Treasurer, & Secombes, 2007;Hsu, 2009;Willett, Cherry, & Steiner, 1997). Thymus organs contain various of cells including lymphocytes, macrophages, epithelial cells, fibroblasts and mastos (Cao, Chen, Lu, Hu, & Wang, 2017;Chun, Schatz, Oettinger, Jaenisch, & Baltimore, 1991;Greenhalgh, Olesen, & Steiner, 1993), and RAG1 expression in mammals was detected higher in thymus organs than that in spleen, liver and bone marrow organs.…”
Section: F I G U R E 4 Electrophotogram Of Rag1mentioning
confidence: 99%